Nutraceutical COMP-4 confers protection against endothelial dysfunction through the eNOS/iNOS-NO-cGMP pathway - Monica G. Ferrini; Andrea Abraham; Revecca Millán; Leslie Graciano; Sriram V. Eleswarapu; Jacob Rajfer (PLoS ONE, 2025)
The nutraceutical COMP-4 –consisting of L-citrulline, ginger extract, and herbal components Paullinia cupana and muira puama–has been shown previously to stimulate the production of nitric oxide (NO) in a variety of tissue types. We hypothesized that COMP-4 may have a protective, stimulatory effect on the vascular endothelial cell. Human umbilical arterial endothelial cells were incubated for 24 hours with or without COMP-4 and, to replicate impairment of endothelial function, co-incubated with or without H2O2. NO intracellular content, nitrite formation and cGMP content in culture media, nitric oxide synthase (NOS) isoforms and mRNA content, pro-inflammatory cytokines, and PAI-1 expression and activity were measured. COMP-4 increased endothelial cell production of NO and cGMP and the expression of both endothelial NOS (eNOS) and inducible NOS (iNOS), in tandem with a reduction in cytokine expression and activity of PAI-1. Co-incubation of COMP-4 with H2O2 reversed detrimental effects of H2O2 on endothelial function, evidenced by improvement in NO availability and abrogation of the pro-inflammatory milieu. These results suggest that COMP-4 exerts a stimulatory effect on endothelial cell eNOS and iNOS to increase NO bioavailability, leading to a reduction in pro-inflammatory cytokines, particularly the prothrombotic PAI-1.